Pyrosequencing for Detection of Lamivudine-Resistant Hepatitis B Virus - Lindström, Anna (American Society for Microbiology, 2004)
Chronic hepatitis B virus (HBV) infection can cause severe liver disease, including cirrhosis and hepatocellular carcinoma. Lamivudine is a relatively recent alternative to alpha interferon for the treatment of HBV infection, but unfortunately, resistance to lamivudine commonly develops during monotherapy. Lamivudine-resistant HBV mutants display specific mutations in the YMDD (tyrosine, methionine, aspartate, aspartate) motif of the viral polymerase (reverse transcriptase [rt]), which is the catalytic site of the enzyme, i.e., methionine 204 to isoleucine (rtM204I) or valine (rtM204V). The latter mutation is often accompanied by a compensatory leucine-to-methionine change at codon 180 (rtL180M). In the present study, a novel sequencing method, pyrosequencing, was applied to the detection of lamivudine resistance mutations and was compared with direct Sanger sequencing. The new pyrosequencing method had advantages in terms of throughput. Experiments with mixtures of wild-type and resistant viruses indicated that pyrosequencing can detect minor sequence variants in heterogeneous virus populations. The new pyrosequencing method was evaluated with a small number of patient samples, and the results showed that the method could be a useful tool for the detection of lamivudine resistance in the clinical setting.